Challenging the Sex Binary in Hegel’s Philosophy - Okazaki, Yuka (Revista Eletrônica Estudos Hegelianos, 2022)
Although there is increasing investigation into Hegel’s account of the sexes, the intricate relation of “intersex” to the concept of sexes remains overlooked or marginalized throughout Hegel’s scholarship. This paper aims to examine Hegel’s conceptions of sexual difference and “intersex” as found in his Jena 1805/06 draft and mature philosophy of nature. For this aim, first, I trace how Hegel incorporates (or fails to incorporate) intersex research by his contemporaries. Second, I explore how Hegel’s view on sex difference changes from his Jena draft to the student’s transcript of his Berlin lectures. Third and finally, I show how Hegel’s critical analysis of classification and definition in his mature philosophy of nature and the Science of Logic intervenes in the “hermaphrodite” or “androgyny” discourses. In doing so, I will argue that Hegel challenges the stubborn and even still rampant belief in the strict sex binary, demonstrating the impossibility of drawing any given or ultimate borderline between the sexes.